2021
DOI: 10.21776/ub.mnj.2021.007.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Effectivity of Nintendo Wii as Rehabilitation Therapy in Post Stroke Patients: A Systematic Review

Abstract: Post stroke patients need medical rehabilitation to live an independent life. Nintendo Wii technology presents an alternative choice that is quite safe, feasible, and has a high potential in rehabilitating & restoring motor function in post stroke patients. Although it has been widely used as adjunct therapy in stroke rehabilitation facilities throughout the world, only a few acknowledge its effectivity in post-stroke patients. This study aims to conduct a systematic review in order to identify and assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Meldrum, D et al (2012) found that approximately 88% of patients would include Nintendo Wii in their future treatments [28]. Furthermore, the use of NWT did not seem to produce side effects, unlike the dizziness, nausea, headache, etc., that seems could appear in immersive VR [29,30]. In addition, NWT is a low-cost, commercialized, and useful tool that allows the training of flexibility, balance, strength, and coordination in safe environments, such as homes or clinical centers [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meldrum, D et al (2012) found that approximately 88% of patients would include Nintendo Wii in their future treatments [28]. Furthermore, the use of NWT did not seem to produce side effects, unlike the dizziness, nausea, headache, etc., that seems could appear in immersive VR [29,30]. In addition, NWT is a low-cost, commercialized, and useful tool that allows the training of flexibility, balance, strength, and coordination in safe environments, such as homes or clinical centers [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…We found that, in those reviews, NWT was the most widely used type of VR intervention, and extensive scientific reports have been written about it. Previous reviews assessed the effect of NWT in improving balance in children with CP [25,37], and in other neurological diseases, such as Parkinson's disease [38,39] or stroke [29,40]. Thus, in comparison with other reviews that assessed all non-immersive VR devices, our aim was to assess whether NWT, as one of the most non-immersive VR devices available, had an effect on improving UE motor function abilities in children with CP.…”
Section: Introductionmentioning
confidence: 99%